Laparoscopic Left Renal Vein Transposition for Nutcracker Syndrome - Guňka, Igor; Navratil, Pavel; Lesko, Michal; Jiska, Stanislav; Raupach, Jan (Annals of vascular surgery, 2016)
The left renal vein (LRV) reimplantation into the distal inferior vena cava is considered to be the gold standard of care for symptomatic nutcracker syndrome (NCS). The vast majority of these surgical procedures are performed by open surgery. Experiences with minimally invasive laparoscopic surgery in this field are very limited. We present a case of a 17-year-old boy with NCS in whom the transposition of the LRV was done laparoscopically. The patient suffered from left flank pain, painful left-sided varicocele, microscopic hematuria, proteinuria, and oligoasthenospermia. There were no intraoperative complications, and the postoperative course was uneventful. At 12-month follow-up, hematuria, left flank pain, and left testicular pain resolved. Duplex ultrasonography revealed patent LRV. Laparoscopic LRV transposition appears to be safe, feasible, and has favorable postoperative course.
Keywords: laparoskopie; Tomography, X-Ray Computed; Humans; Renal Veins; vena cava inferior; Renal Nutcracker Syndrome; Time Factors; Vascular Patency; renální louskáčkový syndrom; mužské pohlaví; Laparoscopy; Phlebography; Ultrasonography, Doppler, Duplex; Adolescent; výsledek terapie; časové faktory; Replantation; Treatment Outcome; Vena Cava, Inferior; lidé; flebografie; mladiství; duplexní dopplerovská ultrasonografie; počítačová rentgenová tomografie; Male; venae renales; replantace; průchodnost cév